Home Learning Environments of Children in Mexico in Relation to Socioeconomic Status - Susperreguy, María Inés; Jiménez Lira, Carolina; Xu, Chang; LeFevre, Jo-Anne; Blanco Vega, Humberto; Benavides Pando, Elia Verónica; Ornelas Contreras, Martha (Frontiers in Psychology, 2021)
We explored the home learning environments of 173 Mexican preschool children (aged 3 – 6 years) in relation to their numeracy performance. Parents indicated the frequency of their formal home numeracy and literacy activities, and their academic expectations for children’s numeracy and literacy performance. Children completed measures of early numeracy skills. Mexican parent-child dyads from families with either high- or low- socioeconomic status (SES) participated. Low-SES parents (n = 99) reported higher numeracy expectations than high-SES parents (n = 74), but similar frequency of home numeracy activities. In contrast, high-SES parents reported higher frequency of literacy activities. Path analyses showed that operational (i.e., advanced) numeracy activities were positively related to children’s numeracy skills in the high- but not in the low-SES group. These findings improve the understanding of the role of the home environment in different contexts and provide some insights into the sources of the variable patterns of relations between home learning activities and children’s numeracy outcomes. They also suggest that socioeconomic status is a critical factor to consider in research on children’s home numeracy experiences.